Morphology, Morphometry and Distribution of Isolated Landforms in Southern Chryse Planitia, Mars. Issue 5 (11th May 2021) - McNeil, Joseph D.; Fawdon, Peter; Balme, Matthew R.; Coe, Angela L.
Abstract: The margin of Chryse Planitia, Mars, contains >10 5 kilometer‐scale mesas, buttes, and plateaus ("mounds"), many of which are found in and around Oxia Planum, the ExoMars 2022 Rover landing site. Despite this, their origins and evolution are unknown. We have analyzed the morphologies and morphometries of 14, 386 individual mounds to: (1) classify them based on their geomorphology; (2) constrain when they formed based on their stratigraphic and spatial relationships; and (3) develop hypotheses for their geological history. The mounds are classified as compound mounds, mesas, clustered mounds, and hills. Mound heights show that their elevations above the plains tend to a maximum height of 500 m. We interpret this as the thickness of a previously continuous layer that extended several hundred kilometers from the southern highlands into Chryse Planitia. Stratigraphy constrains the deposition of this layer to the Early‐Middle Noachian, correlatable to the phyllosilicate‐bearing strata of Mawrth Vallis, with similar layering also observable in some mounds, suggesting a genetic relationship. The mounds sometimes occur in circular arrangements, interpreted as an association with buried impact structures. We propose that the mounds formed through differential erosion after the premound layer was indurated by mineralization from groundwater in areas superposing underlying crustal weaknesses, for example, at buried crater margins. The subsequent differential erosion of this layer preferentially removed areas unaffected by this induration in the Late Noachian‐Early Hesperian leaving the mound population seen at present. These features present accessible three‐dimensional exposures of ancient layered rocks, and so are exciting targets for future study. Plain Language Summary: Thousands of kilometer‐scale "mounds" occur in the Chryse Planitia region of Mars. Until now, we did not know what they were, how old they are, or why they are so abundant. We examined the mounds, classified them based on their shape, and calculated their heights. We estimated the age of the mounds and how they formed using their relationship to other geological features nearby. We find: (1) There are four types of mounds: hills, mesas, clustered mounds, and compound mounds. (2) The mounds are never taller than about 500 m, suggesting they are remnants of a once‐continuous layer about 500 m thick that has been almost completely removed. (3) Finding mounds hundreds of kilometers into Chryse Planitia means that this layer was once extensive. The largest mounds are similar to bedrock types seen around Mawrth Vallis, an area with clear mineralogical evidence of water altering the rocks in the ancient past. We think that similar minerals occur in parts of the premound layer, hardening it so that these areas were left as the mounds we see today once the rest of the layer was eroded. We conclude that the mounds are important "leftover" features from early in Mars' geological history. Key Points: There is a population of >14, 000 mounds in southern Chryse Planitia that we classify as hills, mesas, clustered mounds, and compound mounds The mounds are most likely remnants of an extensive 500 m thick Early‐Mid Noachian layer, correlatable to clay‐rich Mawrth Vallis strata Mineralization from groundwater in regions of high permeability most likely contributed to their apparent preferential preservation